Coffee silverskin extracts: Quantification of 30 bioactive compounds by a new HPLC-MS/MS method and evaluation of their antioxidant and antibacterial activities. (July 2020) - Nzekoue, Franks Kamgang; Angeloni, Simone; Navarini, Luciano; Angeloni, Cristina; Freschi, Michela; Hrelia, Silvana; Vitali, Luca A.; Sagratini, Gianni; Vittori, Sauro; Caprioli, Giovanni
Graphical abstract: Highlights: Silverskin can be used as raw material for the recovery of functional compounds. A new HPLC-MS/MS method has been developed for 30 bioactive compounds of different subclasses. The monitored bioactive compounds represent 1.6–4% of silverskin extracts. Silverskin extracts play a potential role as protective agents against neurodegeneration. Abstract: The research of value-added applications for coffee silverskin (CSS) requires studies to investigate potential bioactive compounds and biological activities in CSS extracts. In this study, different ultrasound‐assisted extraction (UAE) methods have been tested to extract bioactive compounds from CSS. The obtained extracts, were characterized using a new HPLC-MS/MS method to detect and quantify 30 bioactive compounds of 2 classes: alkaloids and polyphenols (including phenolic acids, flavonoids, and secoiridoids). CSS extracts obtained with ethanol/water (70:30) as extraction solvent showed the highest levels ( p  ≤ 0.05) of bioactive compounds (4.01 ± 0.34% w/w). High content of caffeine was observed with levels varying from 1.00% to 3.59% of dry weight of extract (dw). 18 phenolic compounds were detected in CSS extracts with caffeoylquinic acids (3-CQA, 5-CQA and 3, 5-diCQA) as the most abundant polyphenols (3115.6 µg g to –5444.0 µg g −1 ). This study is also one of the first to characterize in-depth flavonoids in CSS revealing the levels of different flavonoids compounds such as rutin (1.63–8.70 µg g −1 ), quercetin (1.53–2.46 µg g −1 ), kaempferol (0.76–1.66 µg g −1 ) and quercitrin (0.15–0.51 µg g −1 ). Neuroprotective activity of silverskin extracts against H2 O2 -induced damage was evaluated for the first time suggesting for methanol and ethanol/water (70:30) extracts a potential role as protective agents against neurodegeneration due to their ability to counteract oxidative stress and maintain cell viability. Silverskin extracts were not inhibiting the growth of anyone of the bacterial species included in this study but data obtained by water extract might deserve a deeper future investigation on biofilm-related activities, such as quorum sensing or virulence factors' expression. From their composition and their evidenced biological activities, CSS extracts could represent valuable ingredients in nutraceutical formulations.